Comparison of Character Education in Malaysian and Indonesian Elementary Schools - Hasan Mahfud; Sri Marmoah; Jenny Indrastoeti SP; Siti Istiati; Sukarno Sukarno; Supianto Supianto; Diah Hayu Novita Sari; Zaharah binti Hashim (Yayasan Keluarga Guru Mandiri, 2023)
Implementation of character education will create superior human resources in all aspects of personality. This study aims to explore the essential core of character education in elementary schools and explore the similarities and differences in character education applied in elementary schools in Malaysia and Indonesia. This research used a descriptive qualitative approach with the comparative method, and the type of research used was library research. Data collection techniques included researching and identifying data through various documents from scientific publications in journals, national and international articles, and applicable laws and regulations. The results of a literature review on character education in elementary schools in Malaysia and Indonesia show similarities and differences in the concepts, programs, and implementation of character education in the two countries.A comparison of character education in Indonesia and Malaysia can be a valuable basis for improving these two countries' character education systems and drawing lessons that can be applied in other countries.